1990
DOI: 10.1016/0301-9322(90)90055-n
|View full text |Cite
|
Sign up to set email alerts
|

Void fraction disturbances in a uniform bubbly fluid

Abstract: The paper is concerned with the flow of dispersions of gas bubbles in liquid, with bubble sizes such that the inertia forces on the bubbles are of importance to the dynamics. One-dimensional conservation equations are derived, which govern the flow when the deviations from the uniform state are small. These are used to describe the features of the propagation of void fraction disturbances, and to investigate the stability of uniform bubbly flows. The results are compared with what has been observed in experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 14 publications
1
74
0
Order By: Relevance
“…The short term result of this instability is the appearance of vertically propagating, horizontally oriented kinematic waves (see chapter 16) in otherwise nominally steady flows. They have been most extensively researched in fluidized beds but have also be observed experimentally in vertical bubbly flows by Bernier (1982), Boure and Mercadier (1982), Kytomaa and Brennen (1990) (who also examined solid/liquid mixtures at large Reynolds numbers) and analyzed by Biesheuvel and Gorissen (1990). (Some further comment on these bubbly flow measurements is contained in section 16.2.3.…”
Section: Inhomogeneity Instability In Vertical Flowsmentioning
confidence: 99%
“…The short term result of this instability is the appearance of vertically propagating, horizontally oriented kinematic waves (see chapter 16) in otherwise nominally steady flows. They have been most extensively researched in fluidized beds but have also be observed experimentally in vertical bubbly flows by Bernier (1982), Boure and Mercadier (1982), Kytomaa and Brennen (1990) (who also examined solid/liquid mixtures at large Reynolds numbers) and analyzed by Biesheuvel and Gorissen (1990). (Some further comment on these bubbly flow measurements is contained in section 16.2.3.…”
Section: Inhomogeneity Instability In Vertical Flowsmentioning
confidence: 99%
“…This model is applied only in the dispersed-phase momentum balance (i.e., P c ) 0) and is defined by Biesheuvel and Gorissen 38 as…”
Section: Review Of Model Formulationmentioning
confidence: 99%
“…33,34 Additionally, several researchers have reported on the prediction of flow-regime transitions using either numerical simulations 35 or linear stability analysis of various model equations. 13,14,[36][37][38][39][40][41][42][43][44][45] It may be noted that the time-dependent Eulerian two-fluid models for homogeneous bubbly flow tend to predict transitions to nonuniform and heterogeneous flow at very low values of the average gas holdup (usually less than 0.2). However, an opposite trend was observed in the recent experiments of Harteveld et al [46][47][48] at Delft University of Technology, who observed homogeneous bubbly flow up to average gas holdups of 0.5.…”
Section: Introductionmentioning
confidence: 99%
“…The BP model is reported in the literature to play an important role in bubblephase stability [18]. Biesheuvel and Gorissen [19] proposed a bubble pressure model of the form:…”
Section: Bubble Pressure Modelmentioning
confidence: 99%